Elmer and the Big Bird - McKee, David (Minneapolis : Andersen Press USA, 2012)
When Elmer the patchwork elephant learns that a bully is bothering the smaller birds, he devises a plan to teach the bully bird a lesson.
Originally published: London : Andersen, 2008.
Ages 4-9.
Keywords: Bullies -- Fiction; Elephants -- Fiction; Birds -- Fiction